Atomic layer deposition of In2O3 transparent conductive oxide layers for application in Cu(In, Ga)Se2 solar cells with different buffer layers. Issue 6 (27th January 2016) - Keller, Jan; Stolt, Lars; Edoff, Marika; Törndahl, Tobias
Abstract : This contribution presents the development of atomic layer deposited (ALD) In2 O3 films for utilization as transparent conductive oxide (TCO) layers in Cu(In, Ga)Se2 (CIGSe) solar cells. The effects of ALD process parameters on the morphology and growth of In2 O3 are studied and related to the electrical and optical properties of the films. Maintaining similar resistivity values compared to commonly used ZnO:Al (AZO) TCOs ( ρ = (5–7) × 10 −4 Ωcm), a superior mobility of μ ≈ 110 cm 2 /Vs could be achieved (more than five times higher than a ZnO:Al reference), which results in a significantly reduced parasitic optical absorption in the infrared region. Application of the optimized In2 O3 layers in CIGSe solar cells with varying buffer layers (CdS and Zn1– x Sn x O y (ZTO)) leads to a distinct improvement in short circuit current density J sc in both cases. While for solar cells containing the ZTO/In2 O3 window structure, a drop in open‐circuit voltage V oc and a deterioration under illumination is observed, the TCO exchange (from AZO to In2 O3 ) on CdS buffer layers results in an increase in V oc without detectable light bias degradation. The efficiency η of the best corresponding solar cells could be improved by about 1% absolute.